Poškodbe baletnih plesalk - Hubej, Tija (Šport (Ljubljana), 2017)
The origins of ballet are traced to the early nineteenth century. The technique has not changed significantly since then and is considered as one of the most sophisticated and physically demanding dance techniques. It symbolizes the basis for any other dance genre or aesthetic sports. That the body can withstand such pressures, it must have a specific characteristics that represent the essence of ballet technique. The purpose of the thesis is the analysis of injuries of ballet dancers from the Conservatory of Music and Ballet Ljubljana. The study included 24 girls aged 15 to 21 years with minimum 7 years of ballet practice. Data was analyzed using Program for Statystical analyzis SPSS (IBM SPSS Statistics). Charts and graphs were presented with Microsoft Excel Programme (Microsoft). The results have shown that the maximum damage 74 % is located on the lower limbs. 13 % of the injuries were located at the backbone and the most injured structures were tendons and bones, followed by the muscles and joints. In general we can conclude that in specific training as injury rate is very high and mostly affects the lower extremities. Also of concern is the fact that the dancers do not pay enough attention to the injuries, or are unaware of the seriousness of the situation.
Keywords: baletke; baletne plesalke; ballerinas; sports injuries; športne poškodbe